ANALYSIS OF FACTORS INFLUENCING LABOR ABSORPTION IN REGENCIES/CITIES IN BALI PROVINCE - I Putu Satya Wiguna; Ida Bagus Putu Purbadarmaja (Adisam Publisher, 2026)
The goal of economic development is to improve the standard of living and welfare of the community. Economic development of a country or region basically involves the process of interaction between various groups of variables, such as human resources, natural resources, technology, capital, and so on. The purpose of the research is toanalyze the simultaneous and partial influence of investment, education, and local revenue on labor absorption in the Regency/City in Bali Province. The quantitative associative research design with the analysis method used in this study is multiple linear regression analysis. The results of the study show 1) aSimultaneous way of investment, education, and PAD significantly influence the absorption of labor in the Bali Province. 2) Partially investment and PAD have a positive and significant effect on the absorption of labor in the Bali Province. 3) Partially education has a negative and insignificant effect on the absorption of labor in the Bali Province.